Sosialisasi Bahaya Bahan Kimia Pada Masyarakat Di Sekitar Pt. Waru Kaltim Plantation (Astra Agro Lestari Group) - Zulfikar, Iwan; Rusba, Komeyni; Noeryanto, Noeryanto (Program Studi D4 K3 Universitas Balikpapan, 2023)
The socialization was carried out in the community around PT. Waru Kaltim Plantation by bringing pictures relating to the dangers of using chemical pesticides which were pasted on cardboard and explained one by one and then distributing flyers to the public. The result achieved is that people are more able to be aware of the dangers of chemicals, especially pesticides that are dangerous. The community has also understood the dangers or diseases caused by the dangers of chemicals, especially pesticides. Housewives around PT. Waru Kaltim Plantation has been able to observe the dangerous characteristics of pesticides.